HIV tropism and its relationship with transmitted resistance in naive patients. (August 2013) - Sterrantino, Gaetana; Zaccarelli, Mauro; Di Giambenedetto, Simona; De Luca, Andrea; Francisci, Daniela; Punzi, Grazia; Monno, Laura; Bruzzone, Bianca; Antinori, Andrea; Zazzi, Maurizio
Aim: The objective of the present study was to investigate whether patients with transmitted resistance more frequently harbor X4/DM tropic viral strains.Patients & methods: Patients were included from an Italian nationwide database if they were tested for tropism and resistance at the same time. HIV tropism was assessed by the Geno2pheno coreceptor system (false-positive rate: ≤10%) and enhanced-sensitivity Trofile assay. Overall, 299 naive patients, tested between 2009 and 2011, were included: 252 patients tested by Geno2pheno, 116 by enhanced-sensitivity Trofile assay and 80 by both methods.Results & conclusion: Using Geno2pheno, X4/DM tropic virus was detected in 55 patients (21.8%), with an overall mean false-positive rate of 42.3% (standard deviation: ±33.3). Using the enhanced-sensitivity Trofile assay, 29 patients (25.0%) carried X4/DM tropic virus. Resistance mutations were more frequently detected in patients harboring X4/DM tropic virus (mean: 1.18 ± 3.0 vs 0.41 ± 1.2 per patient; p = 0.001) and with both Geno2pheno (0.82 ± 2.6 vs 0.35 ± 0.9; p = 0.034) and enhanced-sensitivity Trofile assay (1.11 ± 1.9 vs 0.46 ± 1.1; p = 0.039). However, significant differences were found for reverse transcriptase-related mutations, but not for transmitted protease resistance, and this might be explained by the low frequency of transmitted protease resistance. Among single mutations, L33F and L90M with regards to protease and K65R, K70E, K219E and V106A/M with regards to reverse transcriptase were found to be significantly associated with X4/DM tropic virus. X4/DM tropism was also associated with lower CD4 + cell count, but not with higher HIV RNA levels. X4/DM tropic HIV strains were related to a higher frequency of transmitted reverse transcriptase resistance mutations in this unselected set of naive patients. As a consequence, if a patient harbors a non-CCR5 tropic virus and bears more reverse transcriptase resistance and less protease resistance, a boosted protease inhibitor-based first-line regimen should be preferred.